2001
DOI: 10.1089/107555301300004501
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Outcomes at Alternative Medicine Cancer Clinics: A Feasibility Study

Abstract: Historical, widespread use of clinics such as these with anecdotal reports of extraordinary survival merit prospective, systematic monitoring of patient outcomes. For data to be meaningful, however, disease status must be pathologically confirmed and patient follow-up improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Corresponding 5‐year survivals were 30%, 16% and 18%. Median time from diagnosis of metastatic disease to presentation at the Center (lag time) was 8 months (20). First‐line patients had a median lag time of 3 months, second line patients of 13 months and third‐line or later patients 15 months.…”
Section: Resultsmentioning
confidence: 99%
“…Corresponding 5‐year survivals were 30%, 16% and 18%. Median time from diagnosis of metastatic disease to presentation at the Center (lag time) was 8 months (20). First‐line patients had a median lag time of 3 months, second line patients of 13 months and third‐line or later patients 15 months.…”
Section: Resultsmentioning
confidence: 99%
“…However, research has shown that most patients turn to such options when the orthodox medicine is unable to offer anything more. 46 It would be worth exploring such a dietary regimen in the future and moving away from our conceptual struggle with modern high-tech medicine. We have a responsibility and a professional duty to help patients make the best treatment decisions for themselves, and the only way to do so with regard to the Gerson regimen is to carry out a prospective evaluation of its efficacy in a rigorous manner.…”
Section: Discussionmentioning
confidence: 99%
“…Richardson et al collected prospective outcomes data from several oncology clinics that take a CAM approach to cancer therapy. 26,27 They reported on both the feasibility and challenges of conducting outcomes research of CAM therapies in cancer clinics. Pfeifer and Jonas used a PODS approach to investigate Immuno-Augmentative Therapy (IAT), a CAM therapy used by thousands of cancer patients that had not been previously evaluated in a systematic fashion for either safety or efficacy.…”
Section: Evolution and Development Of Searchmentioning
confidence: 99%